2014
DOI: 10.1002/chin.201420125
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Biological Evaluation of Nimesulide Based New Class of Triazole Derivatives as Potential PDE4B Inhibitors Against Cancer Cells.

Abstract: Some novel 1,2,3-triazole derivatives (V) (9 examples) derived from the non-steroidal antiinflammatory drug nimesulide are designed and synthesized via a multi-step sequence involving a copper-catalyzed azide-alkyne cycloaddition as key step. Two of the title compounds, i.e. (VIa) and (VIb), show promising cytotoxic properties against HCT-15 human colon cancer cells in vitro. -(MAREDDY, J.; NALLAPATI, S. B.; ANIREDDY, J.; DEVI, Y. P.; MANGAMOORI, L. N.; KAPAVARAPU, R.; PAL*, S.; Bioorg. Med. Chem. Lett. 23 (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…antitumoral [8,9] . anticancer [10][11][12] ,antityrosinase [13] , and antiinflammatory [14] activities. Notable drugs based on the 1,2,3-triazole scaffold include Rufinamide, an anticonvulsant, Cefatrizine, an antibiotic, and Tazobactam, an antifungal agent.…”
Section: Introductionmentioning
confidence: 99%
“…antitumoral [8,9] . anticancer [10][11][12] ,antityrosinase [13] , and antiinflammatory [14] activities. Notable drugs based on the 1,2,3-triazole scaffold include Rufinamide, an anticonvulsant, Cefatrizine, an antibiotic, and Tazobactam, an antifungal agent.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] 1,2,3-Triazole systems the ability of hydrogen bond formation, dipoledipole and π stacking interactions, stable to reduction and oxidation. 8 1,2,3-triazoles are present in many of the drugs like theTazobactum,Carboxyamidotriazole and Ru namide etc.The triazoles arereported to have the anticancer 9,10 , antitubercular 11 , antifungal 12,13 antibacterial 14,15 , antiviral 16,17 and antiobesity 18,19 and anti-diabetic 20 properties.…”
Section: Introductionmentioning
confidence: 99%
“…have reported a series of fluconazole‐based mimics accommodate 1,3,4‐oxadiazole and 1,2,3‐triazole moieties and showed that the analogues exhibited significant antifungal activity with MIC 80 ≤ 0.125 μg/mL [27a]. Recently, we have synthesized 1,2,3‐triazole‐etodolac hybrids, etodolac‐pyridazones, and 1,2,3‐triazole‐nimesulides and investigated as anticancer agents .…”
Section: Introductionmentioning
confidence: 99%